3D printed surgical planning prototype manufactured by a hybrid multi-material 3D printer. Issue 1 (October 2021) - Tejo, A; Castellví, A; Lustig, P; Fenollosa, F; Uceda, R; Buj, I; Krauel, L; Valls, A; Munuera, J
Abstract: Surgical planning is a preoperative method of pre-visualization that is carried out before or during a surgical intervention in order to achieve the best outcome. This can be done either image-based or hands-on. Regarding the first strategy, it is based on the use of medical images. However, it has a huge limitation, which is the difficulty of identifying anatomical structures (crucial for surgeons to make correct decisions) and distances between tissues without any physical support. This problem is overcome with the use of 3D models. Despite this important development, until nowadays most of the surgical planning prototypes were 3D printed either using the moulding technique, which might take several days, or high-cost technologies as is material jetting. That is why, the present manuscript seeks to solve the problems arose by the use of a hybrid-multi material 3D printer which can not only use several materials at the time, but also two 3D printing technologies. The prototype introduced in this study is a neuroblastoma, a common cancer among children.